2005
DOI: 10.1111/j.1365-2125.2004.02253.x
|View full text |Cite
|
Sign up to set email alerts
|

Dosing strategy for enoxaparin in patients with renal impairment presenting with acute coronary syndromes

Abstract: BackgroundPhase III clinical studies have confirmed that enoxaparin is superior to standard heparin in reducing the rate of recurrent ischaemic events in patients with non-ST elevation acute coronary syndromes. Patients with moderate to severe renal impairment were, however, excluded from these studies. Due to the hydrophilic disposition of enoxaparin, accumulation is likely in patients with renal dysfunction, thereby increasing the risk of haemorrhagic complications if standard weight adjusted treatment doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 36 publications
9
85
0
2
Order By: Relevance
“…4,5 Because LMWHs are primarily excreted by the kidney, there is concern for bioaccumulation of LMWHs in patients with chronic renal insufficiency receiving repeated doses, in particular with the hydrophilic enoxaparin. 6 However, given the varying molecular and pharmacokinetic features of the LMWHs, results found with one type of LMWH are not necessary applicable to other LMWHs. Sigueret, Pautas, and their group showed that there was no accumulation of anti-factor Xa activity over a 10-day treatment period of therapeutic tinzaparin, and in a subsequent study conducted over 30 days, reported the absence of correlation between anti-Xa levels and creatinine clearance with therapeutic tinzaparin therapy.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Because LMWHs are primarily excreted by the kidney, there is concern for bioaccumulation of LMWHs in patients with chronic renal insufficiency receiving repeated doses, in particular with the hydrophilic enoxaparin. 6 However, given the varying molecular and pharmacokinetic features of the LMWHs, results found with one type of LMWH are not necessary applicable to other LMWHs. Sigueret, Pautas, and their group showed that there was no accumulation of anti-factor Xa activity over a 10-day treatment period of therapeutic tinzaparin, and in a subsequent study conducted over 30 days, reported the absence of correlation between anti-Xa levels and creatinine clearance with therapeutic tinzaparin therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The large-scale clinical studies instrumental in the approval of current dosing enrolled healthier patient populations than those seen in everyday clinical practice and often excluded patients with renal dysfunction. Smaller studies 7,[15][16][17] have made dose modifications to target an antifactor Xa activity therapeutic range, despite a lack of strong evidence correlating antifactor Xa activity target range to outcomes. 18,19 Thus, we conducted a review of medical records to compare the outcomes of bleeding and recurrent thrombotic events in patients with normal renal function vs those with moderate renal impairment who were receiving the manufacturer's recommended therapeutic dose of enoxaparin.…”
Section: Arch Intern Med 2012;172(22):1713-1718mentioning
confidence: 99%
“…Considering the impact of major bleeding as an adverse drug event that may include life-threatening or fatal hemorrhage, we suggest that regulatory agencies, the manufacturer, and/or guidelinewriting organizations explore all available data, published and unpublished, and consider revising dosing and/or monitoring guidelines in patients with moderate renal impairment. Others 7,15,17 have offered alternative dosing strategies and, although use has been investigated in a limited number of patients, these regimens merit consideration ( Table 5).…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study by Green et al suggested that enoxaparin accumulation occurs after steady state is achieved in patients with CrCl ≤ 80 ml/min. This accumulation is especially prominent in the moderate renal impairment range; hence, the authors recommend an empiric dose adjustment based on pharmacokinetic and pharmacodynamic data [16]. However, the package insert only recommends dose reduction at a CrCl<30 ml/min.…”
Section: Introductionmentioning
confidence: 99%